Comparative study of transparent polyimides derived from bis(ether anhydride)s and bis(ester anhydride)s using 2, 2′-bis(trifluoromethyl)biphenyl-4, 4′-diamine. (March 2017) - Zhou, Yu; Chen, Guofei; Wang, Wei; Song, Liping; Fang, Xingzhong
Two series of polyimides (PIs) derived from bis(ether anhydride)s and bis(ester anhydride)s using 2, 2′-bis(trifluoromethyl)biphenyl-4, 4′-diamine were synthesized via solution polycondensation. The poly(ether imide)s could be formed by the conventional one-step method, while the poly(ester imide)s were only afforded by the two-step procedure. The resulting PIs had glass transition temperatures ( T g s) in the range of 224–320°C and exhibited good mechanical properties with tensile strength in the range of 80.5–96.5 MPa, tensile moduli 2.7–6.9 GPa, and elongations at break 1.5–17.3%. It was found that the PIs derived from bis(ether anhydride)s showed higher thermal stability, better solubility, and transparency but lower T g and higher water absorption compared with bis(ester anhydride)-based PIs due to the different ether and ester linkages.